Antibiotic use but not gastrointestinal infection frequently precedes first diagnosis of functional gastrointestinal disorders. Issue 9 (15th October 2021) - Jones, Michael P.; Shah, Ayesha; Walker, Marjorie M.; Koloski, Natasha A.; Holtmann, Gerald; Talley, Nicholas J.
Abstract: Introduction: While the etiopathogenesis of functional gastrointestinal disorders (FGIDs) is not completely understood, alterations of the intestinal microbiome have been observed. Antibiotics can induce dysbiosis, but whether antibiotics are a risk factor for the onset of FGIDs is uncertain. Antibiotics have been reported as both a risk factor for new onset FGID but also as a therapy for existing FGID. This study aimed to estimate the fraction of cases where antibiotics provoked the onset of FGID. Method: Electronic medical records were obtained from general practices (primary care) in the United Kingdom. Dates of antibiotic prescription (AP) were compared with first date of FGID diagnosis and contrasted across three prevalent FGIDs and controls without gastrointestinal disorders. Results: There were 10, 926 GI healthy controls, 4326 IBS alone, 3477 FD alone, 340 chronic constipation and 4402 with overlap of multiple conditions. Both the prevalence of AP and rate were higher in FGID patients and increased with diagnosis of multiple FGIDs. 7%–14% of FGID patients were prescribed their first recorded antibiotic in the 12 months prior to their first FGID diagnosis and 20%–33% were prescribed an antibiotic in the same period. Differences between FGID groups were not accounted for by social deprivation and only rate of AP was moderated by social deprivation. In contrast, only 5%–10% of patients ever had a gastrointestinal infection recorded and only 1.5%–3.5% prior to their first FGID diagnosis. Conclusion: These data indicate that antibiotics are prescribed prior to FGID diagnosis in a significant minority of care‐seeking FGID patients, opening the potential for this medication to contribute to the pathophysiology. APs appears to mostly be for non‐gastrointestinal conditions.